Ch. 249, Subchapter 6-Crimes against Morality, Decency, etc., §193, no. 4 in 1909, Wash. Sess. Laws 942, 947 (1909 E. L. Boardman). - (:unkn) unknown (My University, 1909)
Every person who Shall sell, or give, or permit to be sold or given to any person under the age of eighteen years, any revolver, pistol, or toy pistol Shall be guilty of a gross misdemeanor.
Keywords: TRANSFER - MINORS